2022
DOI: 10.3390/pharmaceutics14071447
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent PLGA Nanocarriers for Pulmonary Administration: Influence of the Surface Charge

Abstract: Nearly four million yearly deaths can be attributed to respiratory diseases, prompting a huge worldwide health emergency. Additionally, the COVID-19 pandemic’s death toll has surpassed six million, significantly increasing respiratory disease morbidity and mortality rates. Despite recent advances, it is still challenging for many drugs to be homogeneously distributed throughout the lungs, and specifically to reach the lower respiratory tract with an accurate sustained dose and minimal systemic side effects. En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…The administration of drugs to the lungs faces challenges in passing through the airway and crossing the mucus barrier. Specifically, tDONs-R9 possess the characteristics of nanomedicines that are more likely to penetrate the mucus network. We were further inspired to investigate the tissue distribution, alveolar deposition effect, and cellular uptake fate of inhaled tDONs-R9 in ALI mice.…”
Section: Biodistribution Cellular Uptake Fate Of Inhaled Tdons-r9 In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The administration of drugs to the lungs faces challenges in passing through the airway and crossing the mucus barrier. Specifically, tDONs-R9 possess the characteristics of nanomedicines that are more likely to penetrate the mucus network. We were further inspired to investigate the tissue distribution, alveolar deposition effect, and cellular uptake fate of inhaled tDONs-R9 in ALI mice.…”
Section: Biodistribution Cellular Uptake Fate Of Inhaled Tdons-r9 In ...mentioning
confidence: 99%
“…DNA origami nanostructure (DON) is an emerging drug platform for the treatment of diseases with the advantage of biocompatibility, biostability, and programmability. Previously, we reported that DON based on efficient self-assembly, well-defined, uniform size, and spatially addressability is a powerful nanomedicine vehicle for cancer therapy. Recent studies have reported the ROS-scavenging capability of DONs and their potential for the treatment of inflammatory injury-related diseases, such as acute kidney injury and rheumatoid arthritis. However, no studies have explored the therapeutic possibility of DONs in lung inflammatory diseases, especially the potential of inhaled therapeutic. According to the studies of drug delivery to lung inflammatory diseases, hydrophilic nanoparticles with a size of 60–300 nm and neutral/negative charge are more likely to penetrate the mucus barrier and deposit to the alveolar region. Notably, DON is not only a ROS scavenger but also a negatively charged hydrophilic nanostructure with a uniform size, which makes it advantageous and promising for inhalation therapy in ALI.…”
mentioning
confidence: 99%
“…Both methods to diagnose in vivo (Ximendes et al, 2021), (Ximendes et al, 2017), (Pellico et al, 2021), (Santos et al, 2020) and ex vivo (Pelaez et al, 2018), (Litti et al, 2021), (Enshaei et al, 2021) enabled by several nanoformulations have revolutionized current medical practices and will continue to improve the crucial ability to diagnose diseases efficiently. In addition, the continuous effort of researchers to understand and exquisitely characterize the fate of NPs in biological system is a crucial foundation for all this work (Carregal-Romero et al, 2021;Areny-Balaguero et al, 2022).…”
Section: Perspectivementioning
confidence: 99%
“…Furthermore, biodegradable polymers, such as poly(lactic-co-glycolic acid) (PLGA), have also been used to develop nanocarriers that resemble EVs in size and morphology. PLGA nanocarriers have been proposed as a potential pulmonary drug delivery system, since they did not exhibit signs of cytotoxicity and showed and excellent lung biodistribution after intratracheal instillation, offering a suitable tool for the treatment of sepsis-induced acute lung injury [126]. Below, several studies are shown that demonstrate the efficacy of this type of nanocarriers for the treatment of sepsis-induced ARDS.…”
Section: Bioinspired Fully Synthetic Evs Prepared By Supramolecular C...mentioning
confidence: 99%